Resilience in Flood Disaster Volunteers in Indonesia: The Role of Self-Efficacy, Empathy, and Social Support - Ida Rahmawati; Dwi Putri Sulistiya Ningsih; Mika Oktarina; Violita Siska Mutiara; Feri Eka Prasetya; Dini Prastyo Wijayanti; Agus Sulistyowati; Ahmad Guntur Alfianto; Manda Marclida Agustin (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Volunteer resilience during flood disasters denotes an individual's capacity to endure, adapt, and psychologically recover from the stressors encountered during emergency responses. This quality is modulated by internal and external determinants, including personal coping mechanisms and external buffering systems. This study examined the relationships between self-efficacy, empathy, social support, and resilience among flood response volunteers in Indonesia. Employing a quantitative, cross-sectional design, the study sampled 70 volunteers from Bengkulu and East Java provinces via purposive sampling technique that met inclusion and exclusion criteria. Data were collected online (via Zoom) using a structured questionnaire. Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC), the self-efficacy via the General Self-Efficacy Scale (GSE), the empathy through the Interpersonal Reactivity Index (IRI), and social support using the Multidimensional Scale of Perceived Social Support (MSPSS). Construct validity was verified via Pearson Product Moment Correlation, and reliability was confirmed using Cronbach's alpha. Statistical evaluation involved univariate and bivariate chi-square test (X²). The findings revealed that self-efficacy, empathy, and social support correlated significantly with the volunteer’s resilience. Specifically, social support demonstrated the strongest association (p = 0.000; OR = 8.457; 95% CI (2.732-26.180)), followed by self-efficacy (p = 0.001; OR = 7.410; 95% CI (2.396-22.917)), and empathy (p = 0.040; OR = 3.319; 95% CI (1.175-9.370)). Strengthening volunteer’s resilience during flood emergencies requires a comprehensive framework. This approach must simultaneously enhance individual psychological capacities and provide sustainable socio-organizational support structures to optimize ongoing disaster relief efforts across Indonesia.